2018
DOI: 10.1007/s10570-018-1733-3
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmotic dewatering of cellulose nanocrystals

Abstract: One of the main challenges for industrial production of cellulose nanocrystals is the high energy demand during the dewatering of dilute aqueous suspensions. It is addressed in this study by utilising electroosmotic dewatering to increase the solid content of suspensions of cellulose nanocrystals. The solid content was increased from 2.3 up to 15.3 wt%, i.e. removal of more than 85% of all the water present in the system, at a much lower energy demand than that of thermal drying. Increasing the strength of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…In electrofiltration, an electric field is applied to influence the filtration of negatively charged CNCs by inducing an electrophoretic force in the direction of the anode, thereby influencing the filter cake growth. At the same time, it also induces motion of the fluid in the direction of the cathode, which drives solid–liquid separation [ 243 , 244 ]. In this process, the electric field is a dominant factor influencing the dewatering rate, exceeding the effect of modifying suspension conditions.…”
Section: Drying and Dewatering Of Cellulosic Nanomaterialsmentioning
confidence: 99%
“…In electrofiltration, an electric field is applied to influence the filtration of negatively charged CNCs by inducing an electrophoretic force in the direction of the anode, thereby influencing the filter cake growth. At the same time, it also induces motion of the fluid in the direction of the cathode, which drives solid–liquid separation [ 243 , 244 ]. In this process, the electric field is a dominant factor influencing the dewatering rate, exceeding the effect of modifying suspension conditions.…”
Section: Drying and Dewatering Of Cellulosic Nanomaterialsmentioning
confidence: 99%
“…Electro-assisted filtration for microfibrillated cellulose (MFC) helps tackle this issue (10-30 mins/100 ml of diluted suspension) but only through an increase in the overall energy consumption (Wetterling et al 2017). Electroosmotic filtration for CNC has been demonstrated to be energy efficient as compared to the thermal methods, however, higher dewatering rates increases these energy requirements and their applicability to CNF remains unknown (Wetterling et al 2018). Other methods using filtration have employed additives such as salts (Sim et al 2015) and wood pieces (Amini et al 2019) to assist in phase separation for CNFs, however their recovery is either not feasible or economically unviable.…”
Section: Spray Dryingmentioning
confidence: 99%
“…[37] Another study showed that by using electro-assisted dewatering of a cellulose nanocrystal suspension, the solid content of the furnish could increase to 15.3 wt%. [38] One interesting approach to dewatering of high MNFC suspensions is to replace the aqueous phase with a foam. During the last decade, foam forming has been extensively studied as an alternative method for the production of high MNFC content products with high bulk and strength properties, such as in Styrofoam replacements.…”
Section: Introductionmentioning
confidence: 99%